Pengaruh Bonggol Pisang (Musa Balbisiana Colla) sebagai MOL dan Lama Perendaman terhadap Pertumbuhan Mucuna bracteata - Dini Ariyska; Bayu Pratomo; Rama R. Sitinjak; Abednego S. Karosekali; Laura J. Pinem; Edy Fachrial (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Ariyska D, Pratomo B, Sitinjak RR, Karosekali SA, Pinem JL, & Fachrial E. 2020. The effect of banana weevil (Musa balbisiana Colla) as MOL and soaking time on the growth of mucuna bracteata. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aims to determine the effect of concentration and soaking time of MOL banana weevil (Musa balbisiana Colla) on the growth of Mucuna bracteata. The banana species used in this study were bananas with seeds, and grew in abundance in several plantation areas. So that the potential is very disturbing to the main crop, namely oil palm, in other words it becomes a weed in plantations. In this study, bananas were used as a source of MOL. This study used an experimental method with a factorial randomized block design with 2 replications and 16 treatments. The first factor is the concentration of MOL banana weevil (Musa balbisiana Colla) (M) with 4 levels: M0 (0%), M1 (15%), M2 (30%), M3 (45%), the second factor is immersion time (P) with 4 levels: P0 (immersion), P1 (15 minutes), P2 (30 minutes), P3 (45 minutes). The data obtained were analyzed by means of analysis of variance with a significance of 5%. The results of data processing showed that anova did not significantly affect the interaction between the MOL concentration of banana weevil (Musa balbisiana Colla) and the immersion time on the growth of Mucuna bracteata. Various concentrations of banana weevil MOL (Musa balbisiana Colla) and soaking time did not significantly affect the growth of Mucuna bracteata plants. However, physically the growth of Mucuna bracteata is good, so that the presumption arises that this MOL actually acts as a nutrient/fertilizer for plants. Not as a growth regulator as the initial target of the research.